If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -11c = 6 + -12c Solving -12 + -11c = 6 + -12c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '12c' to each side of the equation. -12 + -11c + 12c = 6 + -12c + 12c Combine like terms: -11c + 12c = 1c -12 + 1c = 6 + -12c + 12c Combine like terms: -12c + 12c = 0 -12 + 1c = 6 + 0 -12 + 1c = 6 Add '12' to each side of the equation. -12 + 12 + 1c = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 1c = 6 + 12 1c = 6 + 12 Combine like terms: 6 + 12 = 18 1c = 18 Divide each side by '1'. c = 18 Simplifying c = 18
| -5k+4=-5-6k | | -2n^2-18n-40=0 | | 15y-7=13y+17 | | 13m-9m+1=13 | | -19r+2=14-20r | | -20u+4u+-12=4 | | 3x+2x+80=360 | | 3q-2q=13 | | 17n-9n=16 | | -6+8m=-12+11m | | Y^2+6y=100 | | 3(d-13)-5=1 | | 14=2(p-3) | | 5x+12=-6x+8 | | -4(q+19)=0 | | xb-ba=bc | | 8t-6t=14 | | 12/r=4 | | 8j=12j-8 | | 8=6-x | | x=sin-1(0.5) | | xa-b=x-ba | | y=6.3x+26.9 | | f(x)=2x^2+22x+56 | | 14x-32=-2x | | x*2.5=x+3.6 | | 7a^2+50a=7 | | x^2-17x+14=-6x-4 | | m=-3,b=8/3 | | x^2+11x-12=8x-2 | | 0=-16t^2+24-18 | | x-3x/5=40 |